2021
DOI: 10.1111/rec.13392
|View full text |Cite
|
Sign up to set email alerts
|

Tidal restoration of a managed wetland in California favors non‐native fishes

Abstract: Tidal wetland restoration is commonly used to recover ecosystem functions and services that were lost when wetlands were diked for reclamation or management. Less research has been conducted on the response of invertebrate and fish assemblages to tidal restoration than on plants and physical attributes. Blacklock Marsh, a wetland in Suisun Marsh, USA, was once managed for waterfowl hunting and cattle grazing until its dike was breached, restoring full tidal action. We sampled water quality, zooplankton, macroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
0
1
0
Order By: Relevance
“…Mississippi silverside, largely considered an undesirable nuisance species in the San Francisco Estuary due to competitive and predatory effects on native fishes (Williamson et al 2015;Schreier et al 2016), were frequently encountered in the intertidal basin but were not encountered in the dendritic wetland. Mississippi silverside colonization of restored habitats is largely seen as an unwelcome potential outcome of restoration efforts in the Delta (Herbold et al 2014;Sherman et al 2017;Williamshen et al 2021). While the goals of restoration will be system specific, our results suggest that restored tidal wetland habitats, regardless of configuration, improve regional diversity and support both native and non-native species, which can serve as a useful starting point in making informed management choices.…”
Section: Species-specific Responsesmentioning
confidence: 68%
“…Mississippi silverside, largely considered an undesirable nuisance species in the San Francisco Estuary due to competitive and predatory effects on native fishes (Williamson et al 2015;Schreier et al 2016), were frequently encountered in the intertidal basin but were not encountered in the dendritic wetland. Mississippi silverside colonization of restored habitats is largely seen as an unwelcome potential outcome of restoration efforts in the Delta (Herbold et al 2014;Sherman et al 2017;Williamshen et al 2021). While the goals of restoration will be system specific, our results suggest that restored tidal wetland habitats, regardless of configuration, improve regional diversity and support both native and non-native species, which can serve as a useful starting point in making informed management choices.…”
Section: Species-specific Responsesmentioning
confidence: 68%
“…To compare the potential effect of clams to the effect of jellyfish, we calculated the mean and maximum combined filtration rates by region and water year type, then divided by the average depth per region to calculate the water column turnover rate for the region per day. To obtain grazing rates (i.e., the estimated amount of chlorophyll grazed), we combined the water turnover rates above with data collected by long-term monitoring surveys throughout the region, which have been previously combined and made available on the Environmental Data Initiative data repository (Bashevkin, Perry, et al 2023), with data from the UCD Suisun Marsh Fish Study (collected for Montgomery 2017; Williamshen et al 2021) and the Directed Outflow Project (Schultz and Kalmbach 2023). We then estimated the potential carbon consumed per day by assuming a 32:1 C:Chla ratio (as estimated by Lucas and Thompson 2012), and multiplying carbon density by the water column turnover rates to calculate potential carbon consumed per day.…”
Section: + Random(month)mentioning
confidence: 99%
“…However, previous research has shown that without active management or under certain conditions, restoration efforts may unintentionally favor non-native species and promote native species declines (Grimaldo et al 2012;Williamshen et al 2021). For example, the reintroduction of tidal exchange followed by passive restoration at Blacklock Marsh, located west of the West Delta, was found to provide extensive habitat for Mississippi Silverside, and this species dominated the fish assemblage (Williamshen et al 2021). Additionally, fish assemblages within three restored marshes in the South Delta were found to be dominated by non-native species, specifically centrarchids, Mississippi Silversides, and Threadfin Shad (Grimaldo et al 2012).…”
Section: Habitat Restorationmentioning
confidence: 99%